Irrigators’ willingness to pay for the adoption of soil moisture monitoring tools in South-Eastern Africa - Abebe, F.; Zuo, A.; Ann Wheeler, S.; Bjornlund, Henning; Rooyen, Andre F. van; Pittock, J.; Mdemu, M.; Chilundo, M. (Informa UK Limited, 2020)
Contingent valuation is used to elicit irrigators’ willingness to pay for soil moisture tools in irrigation schemes in Africa, with various econometric methods employed to mitigate potential bias. Key results include that there is a neighbourhood effect influencing adoption, and that being located downstream and spending more on irrigation water positively and statistically significantly influenced willingness to pay for tools. The result suggests that although focusing on economic incentives and promoting farmer learning by those using the tools may promote greater adoption, there is likely to still be a need for co-investment by other bodies.